Exploring the Determinants of Multidrug-Resistant Tuberculosis in Pulmonary TB Patients at Jatisari Karawang: A Cross-Sectional Analysis - Syafila, Vita Afni; Syamsiah, Nita; Hodijah, Lilis Siti; Nurjanah, Uun (STIKep PPNI Jawa Barat, 2025)
Aims: The aim of this study is to find out what factors contribute to the spread of Multidrug-Resistant Tuberculosis (MDR-TB) at Jatisari Karawang Hospital. It focuses on things like nutrition, patient adherence to treatment, motivation, family support, and how treatment is supervised. Methods: This study uses a quantitative method with a cross-sectional approach, which looks at the relationship between risk factors and their effects at one time. It involves 249 patients who visited the MDR-TB clinic at Jatisari Regional Hospital in January 2024, with a sample size of 106 patients. The goal is to identify the factors that are linked to MDR-TB at the hospital in 2024. Result: Most people in the study were under 60, and more males had MDR-TB. Many had poor nutrition (77.4%) and didn’t follow their medication (55.7%). Over half had low motivation (57.5%) and lacked family support (72.6%). About half had poor medication supervision (50.9%). These issues all played a role in the spread of MDR-TB. Conclusion: In conclusion, most people in the study were under 60, male, had a junior high school education, and were unemployed. The study also found that factors like nutrition, taking medication correctly, motivation, family support, and medication supervision are linked to the spread of MDR-TB.